Adnexal Masses in Pregnancy: Study At a Tertiary Care Centre - Dr Samar Mukhtar; Dr Fariha Aman (Innovative Journal of Medical and Health Sciences, 2023)
Adnexal masses are not uncommon in pregnancy. They are often discovered incidentally during routine ultrasound examinations. Adnexal masses are usually asymptomatic, but sometimes can be responsible for abdominal or pelvic pain. Transvaginal and transabdominal ultrasound is essential to define the morphology of pelvic masses. Materials And Methods: This was an observational study carried out at the Department of Obstetrics and Gynecology, at Government Lalla Ded Hospital , Government Medical College , Srinagar over a duration of 9 months from Jan 2022 to September 2022. 43 Pregnant females, irrespective of gestational age , with adnexal masses were included in the study. Results: Serous cystadenomas were the most common histopathologic finding followed by Dermoid cyst and Endometriomas.